Hfq mutation confers increased cephalosporin resistance in Klebsiella pneumoniae - Li Xinran; Yang Mingjuan; Ke Yuehua; Liu Mingyuan; Wang Yufei; Liu Shiwei; Bo Liu; Chen Zeliang (Archives of Biological Sciences, 2017)
Klebsiella pneumoniae (K. pneumoniae), is an opportunistic pathogen raising significant public health concerns owing to its multi-drug resistance. Hfq, one of the main RNA-binding proteins, is a key post-transcriptional regulator. This protein is closely related to virulence and resistance in various pathogenic bacteria. Although the role of hfq in K pneumoniae virulence has been explored, its influence on resistance remains largely unknown. The aim of this study was to investigate the role of hfq in the resistance of K. pneumoniae to cephalosporins. An hfq mutant was constructed, and its resistance to cephalosporins was investigated. The hfq mutant exhibited over 16-fold higher cephalosporin resistance than that exhibited by the wild type. Time-kill curve analysis showed that the hfq mutant could survive under higher concentrations of cephalosporins than the wild-type strain could. Quantitative RT-PCR showed that expression levels for 8 out of the 9 penicillin-binding proteins, which are the targets of cephalosporins, were downregulated in the hfq mutant. Taken together, contrary to its role in many other bacteria, hfq is involved in a negative regulation of K. pneumoniae resistance to cephalosporins by downregulating the expression of penicillin-binding proteins.